Thermoelastic Modeling with Dual Porosity Interacting with an Inviscid Liquid - Rajesh Kumar; Vijayata Pathania; Vipin Gupta; M.S. Barak; Hijaz Ahmad (Journal of applied and computational mechanics, 2024)
This study introduces a two-dimensional thermoelastic model for a homogeneous isotropic half-space with double porosity underlying an inviscid liquid half-space featuring temperature variations. The model incorporates the three-phase lag (TPL) heat equation and reveals that in the solid half-space, four coupled longitudinal waves intertwine with one uncoupled transverse wave, while one mechanical wave ripples through the liquid half-space. The investigation highlights dispersion, attenuation, and other effects affected by the thermal properties and the presence of voids. Using plane wave solutions and boundary conditions at the interface, a concise expression for the frequency equation of the model has been derived. Furthermore, the magnitudes of the displacements in the solid half-space and liquid half-spaces, the temperature change, and the volume fractional fields at the interface have been precisely determined. In the graphical section, computer-simulated results of various wave profiles for magnesium crystal material have been generated for different heat conduction thermoelastic models. The study's implications span various fields, such as hydrology, engineering, ultrasonics, navigation, and electronics.